Implementasi Material Kayu pada Interior Café Latte di Madiun - Linda Novitasari (Intra, 2016)
The building of Café Latte Madiun was formerly a vacant building that was converted to a café which had undergone many changes in terms of its very unique material used in its interior. This study aims to determine and describe the application of materials in terms of furniture and design elements. The qualitative research with descriptive analysis, showed the results at Café Latte Madiun where application of teak wood materials is very dominant, the teak wood used is teak wood waste because the texture and shape are very beautiful and is supported by the application of other materials to the design element.